Degradable environment-friendly modified plastic master batch and preparation method thereof

By introducing 2-methacryloyloxyethylphosphate-choline-grafted polypropylene and MOFs modified carbon fibers into polylactic acid and polypropylene blended composite materials, modifying plastic masterbatches are prepared, solving the problem of poor mechanical properties of the composite materials and achieving better mechanical properties, antibacterial properties and biodegradability.

CN119613853APending Publication Date: 2025-03-14HUNAN DENGKE MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411551547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The mechanical properties of existing polylactic acid and polypropylene blended composite materials are poor, resulting in insufficient mechanical properties in practical applications.

Method used

Polypropylene and polylactic acid are used as the basic resin, 2-methacryloyloxyethylphosphate choline grafted polypropylene as the compatibilizer, and MOFs modified carbon fiber as the reinforcement material. It is melt blended and extruded through a twin-screw extruder to prepare modified plastic masterbatches.

Benefits of technology

It improves biodegradability and mechanical properties, enhances the interface bonding strength of composite materials, improves antibacterial performance, expands the application field, and shows obvious performance advantages and technical competitiveness in actual applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115224070000081
    Figure BDA0005115224070000081
  • Figure BDA0005115224070000091
    Figure BDA0005115224070000091
Patent Text Reader

Abstract

The invention discloses a degradable environment-friendly modified plastic master batch and a preparation method thereof, and belongs to the technical field of plastic master batches, the plastic master batch comprises the following raw materials by weight: 100 parts of polypropylene, 40-50 parts of polylactic acid, 10-20 parts of MOFs modified carbon fiber, 5-10 parts of a compatibilizer, and 1-3 parts of an antioxidant; and the compatibilizer is 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene. The preparation method comprises the following steps: uniformly mixing the raw materials, and carrying out melt extrusion. Polypropylene and polylactic acid are used as basic resin, 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene is used as a compatibilizer, and MOFs modified carbon fiber is used as a reinforcing material to prepare the modified plastic master batch which has good biodegradability and mechanical properties; the method has obvious performance advantages and technical competitiveness in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of plastic masterbatches, and in particular relates to a degradable and environmentally friendly modified plastic masterbatch and a preparation method thereof. Background Art

[0002] Degradable plastics refer to plastics that maintain the basic properties of ordinary plastics for a period of time, but after a certain period of time, they self-degrade and disappear under the action of light or microorganisms. Their decomposition products are water, carbon dioxide and other substances that do not pollute the environment. According to the difference in degradation methods, degradable plastics are divided into photodegradable plastics, biodegradable plastics and photo-biodegradable plastics. Among them, most of the initiators of photodegradable plastics and photo-biodegradable plastics are harmful to the human body, which greatly limits their scope of application. The raw materials of biodegradable plastics are greener, cause less pollution to the environment, and have a shorter degradation cycle.

[0003] Polylactic acid has good heat resistance, spinnability and flexibility, and is the most common biodegradable material. The preparation of composite materials by blending polylactic acid with petroleum-based materials such as polypropylene can retain the degradation performance of the composite materials on the one hand, and on the other hand, the introduction of polypropylene can reduce costs and improve the comprehensive performance of the composite materials. However, polylactic acid and polypropylene are thermodynamically incompatible systems, which are prone to phase separation during the blending process, forming stratification or peeling, resulting in poor mechanical properties of the composite materials. Summary of the invention

[0004] The purpose of the present invention is to provide a degradable and environmentally friendly modified plastic masterbatch and a preparation method thereof, aiming to solve the problem that the existing polylactic acid and polypropylene blended composite materials have poor mechanical properties.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] In a first aspect, the present invention provides a degradable and environmentally friendly modified plastic masterbatch, wherein the degradable and environmentally friendly modified plastic masterbatch comprises the following raw materials in parts by weight:

[0007] 100 parts of polypropylene, 40-50 parts of polylactic acid, 10-20 parts of MOFs modified carbon fiber, 5-10 parts of compatibilizer, and 1-3 parts of antioxidant.

[0008] Preferably, the compatibilizer is 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene.

[0009] Preferably, the preparation method of the compatibilizer comprises the following steps:

[0010] Add polypropylene to a xylene solution of benzophenone, soak at 75°C for 45-60 minutes, take out, and vacuum dry for 1 hour in the dark to obtain pretreated polypropylene;

[0011] Dissolve 2-methacryloyloxyethyl phosphorylcholine in degassed pure water to prepare a graft solution and transfer it to a glass container. Pass nitrogen to deoxygenate. Add pretreated polypropylene to the graft solution. Irradiate under ultraviolet light for 30-45 minutes and then filter. Wash the filter cake with 50°C ethanol solution and vacuum dry.

[0012] Preferably, the usage ratio of polypropylene to the xylene solution of benzophenone is 1 g:30-50 mL, and the concentration of benzophenone in the xylene solution of benzophenone is 0.2 mol / L.

[0013] Preferably, the ratio of the graft solution to the pretreated polypropylene is 30-50 mL: 1 g, and the concentration of 2-methacryloyloxyethyl phosphorylcholine in the graft solution is 0.5 mol / L.

[0014] Preferably, the ultraviolet light irradiation treatment uses a 500W ultra-high pressure mercury lamp, and the wavelength of the ultraviolet light is 300-400nm.

[0015] Preferably, the method for preparing the MOFs modified carbon fiber comprises the following steps:

[0016] S1, adding silver nitrate, copper nitrate trihydrate, 5-hydroxyisophthalic acid, 2-methylimidazole, 1,10-phenanthroline and DMF into deionized water, and ultrasonically treating at room temperature for 30 minutes to obtain an electrophoresis solution;

[0017] S2. Using the acidified carbon fiber as cathode and the metal copper rod as anode, electrophoretic deposition is performed on the surface of the acidified carbon fiber in an electrophoretic solution at room temperature. After the battery deposition, the acidified carbon fiber is dried at 60-90°C for 24 hours and chopped to a length of 3-7 mm to obtain MOFs modified carbon fiber.

[0018] Preferably, the amount ratio of silver nitrate, copper nitrate trihydrate, 5-hydroxyisophthalic acid, 2-methylimidazole, 1,10-phenanthroline, DMF and deionized water in the electrophoresis solution is 25mmol:50mmol:50mmol:50mmol:1mmol:1L:0.33L.

[0019] Preferably, during the electrophoretic deposition process, the distance between the cathode and the anode is 1-5 cm, the voltage during electrodeposition is 4-10 V, and the deposition time is 30 min.

[0020] Preferably, the method for preparing the acidified carbon fiber comprises the following steps:

[0021] A 65wt% nitric acid solution and deionized water were mixed in a volume ratio of 2:1. The carbon fiber was immersed for 2 hours, then the carbon fiber was taken out and dried to obtain acidified carbon fiber. The main purpose of the acid treatment was to increase the surface roughness of the fiber and improve the reaction activity of the fiber surface, so as to prepare for the subsequent growth of MOFs.

[0022] Preferably, the carbon fiber filament is T300 produced by Toray Industries, Ltd., with a diameter of 0.7 um.

[0023] Preferably, the antioxidant is any one of antioxidant 1010, antioxidant 168 and antioxidant 1790, or a mixture of several of them.

[0024] In a second aspect, the present invention provides a method for preparing a degradable and environmentally friendly modified plastic masterbatch, the preparation method comprising the following steps:

[0025] According to the formula ratio, polypropylene, polylactic acid, MOFs modified carbon fiber, compatibilizer and antioxidant are added to the mixer, stirred and mixed at a temperature of 25-40°C and a rotation speed of 150-300 rpm for 15-30 minutes, and then transferred to a twin-screw extruder for melt blending and extrusion granulation to obtain a degradable and environmentally friendly modified plastic masterbatch.

[0026] Preferably, the operating temperature of the twin-screw extruder is 170-190° C., and the screw speed is 250-350 rpm.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention uses polypropylene and polylactic acid as base resins, 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene as a compatibilizer, and MOFs modified carbon fiber as a reinforcing material to prepare a modified plastic masterbatch, which has good biodegradability and mechanical properties and has obvious performance advantages and technical competitiveness in practical applications.

[0029] (2) The present invention adopts cathode electrodeposition to in situ grow Ag, Cu bimetallic MOFs materials on the surface of carbon fiber to obtain MOFs modified carbon fiber. The porous structure and large specific surface area of ​​MOFs help to increase the contact area and interaction force between carbon fiber and resin matrix, thereby improving the interfacial bonding strength of the composite material and enhancing the mechanical properties. The antibacterial properties of Ag, Cu bimetallic MOFs also give the composite material an inhibitory effect on bacteria, which helps to expand the application field of the composite material.

[0030] (3) The compatibilizer in the present invention is 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene, which contains polar groups and can improve the interaction between polypropylene and polylactic acid, thereby improving the mechanical properties of the composite material. Since the molecular structure of 2-methacryloyloxyethyl phosphorylcholine contains a quaternary ammonium salt structure, it is beneficial to improve the antibacterial properties of the composite material. In addition, the molecular structure of 2-methacryloyloxyethyl phosphorylcholine contains nitrogen and phosphorus. During the biodegradation process of the composite material, nitrogen and phosphorus can serve as nutrients for microorganisms, accelerate the growth of microorganisms, promote microbial reproduction, and increase the biodegradation of the composite material. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The polypropylene in this application is brand B4808, which comes from Sinopec Yanshan Petrochemical Company, the polylactic acid is brand REVODE190, which comes from Zhejiang Hisun Biomaterials Co., Ltd., and the carbon fiber is T300 produced by Toray Industries, Ltd., with a diameter of 0.7um.

[0033] Preparation Example 1

[0034] The preparation of the compatibilizer comprises the following steps:

[0035] 10 g of polypropylene was added into 300 mL of a xylene solution containing 0.2 mol / L benzophenone, and the mixture was soaked at 75°C for 45 min, and then taken out and dried under vacuum in the dark for 1 h to obtain pretreated polypropylene.

[0036] Dissolve 2-methacryloyloxyethyl phosphorylcholine in degassed pure water to prepare a graft solution with a concentration of 0.5 mol / L and transfer it to a glass container. Deoxygenate with nitrogen. Add 10 g of pretreated polypropylene to 300 mL of the graft solution. Irradiate under a 500W ultra-high pressure mercury lamp and 300-400nm ultraviolet light for 30 minutes and then filter. Wash the filter cake with a 50°C ethanol solution and dry it in vacuum.

[0037] Preparation Example 2

[0038] The preparation of the compatibilizer comprises the following steps:

[0039] 10 g of polypropylene was added into 500 mL of a xylene solution containing 0.2 mol / L benzophenone, and the mixture was soaked at 75°C for 60 min, and then taken out and dried under vacuum in the dark for 1 h to obtain pretreated polypropylene.

[0040] Dissolve 2-methacryloyloxyethyl phosphorylcholine in degassed pure water to prepare a graft solution with a concentration of 0.5 mol / L and transfer it to a glass container. Deoxygenate it with nitrogen. Add 10 g of pretreated polypropylene to 500 mL of the graft solution. Irradiate it under a 500W ultra-high pressure mercury lamp and 300-400nm ultraviolet light for 45 minutes and then filter. Wash the filter cake with a 50°C ethanol solution and dry it in vacuum.

[0041] Comparative Example 1

[0042] On the basis of Preparation Example 1, the 2-methacryloyloxyethyl phosphorylcholine in Preparation Example 1 was replaced by acrylic acid, and the remaining raw materials, parameters and preparation process were the same as those in Preparation Example 1.

[0043] Preparation Example 3

[0044] The preparation of MOFs modified carbon fiber comprises the following steps:

[0045] S1, adding 25 mmol silver nitrate, 50 mmol copper nitrate trihydrate, 50 mmol 5-hydroxyisophthalic acid, 50 mmol 2-methylimidazole, 1 mmol 1,10-phenanthroline and 1 L DMF into 0.33 L deionized water, and ultrasonically treating at room temperature for 30 min to obtain an electrophoresis solution;

[0046] S2. The acidified carbon fibers were wound in parallel on a polytetrafluoroethylene plate as a cathode and a metal copper rod as an anode. The surface of the acidified carbon fibers was subjected to electrophoretic deposition in an electrophoretic solution at room temperature. The distance between the cathode and the anode was 1 cm. The voltage during electroplating was 4 V and the deposition time was 30 min. After the battery deposition, the acidified carbon fibers were dried at 60 ° C for 24 h and chopped to a length of 3-7 mm to obtain MOFs modified carbon fibers.

[0047] The preparation method of the acidified carbon fiber comprises the following steps:

[0048] A 65wt% nitric acid solution and deionized water were mixed in a volume ratio of 2:1, and the carbon fiber was immersed in the mixture for 2 hours. After that, the carbon fiber was taken out and dried to obtain the acidified carbon fiber.

[0049] Preparation Example 4

[0050] The preparation of MOFs modified carbon fiber comprises the following steps:

[0051] S1, adding 25 mmol silver nitrate, 50 mmol copper nitrate trihydrate, 50 mmol 5-hydroxyisophthalic acid, 50 mmol 2-methylimidazole, 1 mmol 1,10-phenanthroline and 1 L DMF into 0.33 L deionized water, and ultrasonically treating at room temperature for 30 min to obtain an electrophoresis solution;

[0052] S2. The acidified carbon fibers were wound in parallel on a polytetrafluoroethylene plate as a cathode and a metal copper rod as an anode. The surface of the acidified carbon fibers was subjected to electrophoretic deposition in an electrophoretic solution at room temperature. The distance between the cathode and the anode was 5 cm. The voltage during electroplating was 10 V and the deposition time was 30 min. After the battery deposition, the acidified carbon fibers were dried at 90 ° C for 24 h and chopped to a length of 3-7 mm to obtain MOFs modified carbon fibers.

[0053] The preparation method of acidified carbon fiber is the same as that of Preparation Example 3.

[0054] Comparative Example 2

[0055] On the basis of Preparation Example 3, the silver nitrate in Preparation Example 3 was replaced by an equal molar amount of copper nitrate trihydrate, and the remaining raw materials, parameters and preparation process were the same as Preparation Example 3.

[0056] Comparative Example 3

[0057] On the basis of Preparation Example 3, the copper nitrate trihydrate in Preparation Example 3 was replaced by an equal molar amount of silver nitrate, and the remaining raw materials, parameters and preparation process were the same as Preparation Example 3.

[0058] Comparative Example 4

[0059] This comparative example is an acidified carbon fiber, and the specific preparation process is the same as that of Preparation Example 3, with a length of 3-7 mm.

[0060] Example 1

[0061] A degradable and environmentally friendly modified plastic masterbatch, comprising the following raw materials in parts by weight:

[0062] 100 parts of polypropylene, 40 parts of polylactic acid, 10 parts of MOFs modified carbon fiber of Preparation Example 3, 5 parts of compatibilizer of Preparation Example 1, and 10101 parts of antioxidant.

[0063] The method for preparing the above-mentioned degradable and environmentally friendly modified plastic masterbatch comprises the following steps:

[0064] According to the formula ratio, polypropylene, polylactic acid, MOFs modified carbon fiber, compatibilizer and antioxidant 1010 were added to the mixer, stirred and mixed at 25°C and 150rpm for 15 minutes, then transferred to a twin-screw extruder for melt blending and extrusion granulation. The five-stage temperature was 175°C, 180°C, 190°C, 190°C, and 170°C, respectively, and the screw speed was 250rpm to obtain a degradable and environmentally friendly modified plastic masterbatch.

[0065] Example 2

[0066] A degradable and environmentally friendly modified plastic masterbatch, comprising the following raw materials in parts by weight:

[0067] 100 parts of polypropylene, 45 parts of polylactic acid, 15 parts of MOFs modified carbon fiber of Preparation Example 4, 8 parts of compatibilizer of Preparation Example 1, and 1682 parts of antioxidant.

[0068] The method for preparing the above-mentioned degradable and environmentally friendly modified plastic masterbatch comprises the following steps:

[0069] According to the formula ratio, polypropylene, polylactic acid, MOFs modified carbon fiber, compatibilizer and antioxidant 168 were added to the mixer, stirred and mixed at 30°C and 200rpm for 20min, then transferred to a twin-screw extruder for melt blending and extrusion granulation. The five-stage temperature was 175°C, 180°C, 190°C, 190°C, and 170°C, respectively, and the screw speed was 300rpm to obtain a degradable and environmentally friendly modified plastic masterbatch.

[0070] Example 3

[0071] A degradable and environmentally friendly modified plastic masterbatch, comprising the following raw materials in parts by weight:

[0072] 100 parts of polypropylene, 50 parts of polylactic acid, 20 parts of MOFs modified carbon fiber of Preparation Example 4, 10 parts of compatibilizer of Preparation Example 2, and 17903 parts of antioxidant.

[0073] The method for preparing the above-mentioned degradable and environmentally friendly modified plastic masterbatch comprises the following steps:

[0074] According to the formula ratio, polypropylene, polylactic acid, MOFs modified carbon fiber, compatibilizer and antioxidant 1790 were added to the mixer, stirred and mixed at 40°C and 300rpm for 30min, then transferred to a twin-screw extruder for melt blending and extrusion granulation. The five-stage temperature was 175°C, 180°C, 190°C, 190°C, and 170°C, respectively, and the screw speed was 350rpm to obtain a degradable and environmentally friendly modified plastic masterbatch.

[0075] Comparative Example 1

[0076] A degradable and environmentally friendly modified plastic masterbatch is disclosed. Compared with Example 1, the compatibilizer in Example 1 is replaced with a product prepared in Control Example 1, and the remaining raw materials, parameters and preparation process are the same as in Example 1.

[0077] Comparative Example 2

[0078] A degradable and environmentally friendly modified plastic masterbatch is disclosed. Compared with Example 1, the MOFs-modified carbon fiber in Example 1 is replaced with a product prepared in Control Example 2, and the remaining raw materials, parameters and preparation process are the same as in Example 1.

[0079] Comparative Example 3

[0080] A degradable and environmentally friendly modified plastic masterbatch is disclosed. Compared with Example 1, the MOFs-modified carbon fiber in Example 1 is replaced with a product prepared in Control Example 3, and the remaining raw materials, parameters and preparation process are the same as in Example 1.

[0081] Comparative Example 4

[0082] A degradable and environmentally friendly modified plastic masterbatch. Compared with Example 1, the MOFs modified carbon fiber in Example 1 is replaced by the substance in Control Example 4, and the other raw materials, parameters and preparation process are the same as in Example 1.

[0083] The modified plastic masterbatches obtained in Examples 1 to 3 and Comparative Examples 1 to 4 were respectively injection molded at 200°C to form standard specimens, and tensile tests were performed using an electronic tensile machine with reference to GB / T 10403-2006 standard, with a tensile rate of 50 mm / min. The cantilever beam notched impact performance was tested with reference to GB / T1843-2008B standard using a pendulum impact tester. The antibacterial and biodegradable properties were tested with reference to the test steps disclosed in the patent application with application number 202211198209.4. The results are shown in Table 1:

[0084] Table 1

[0085]

[0086]

[0087] It can be seen from the test results in Table 1 that the mechanical properties, antibacterial properties and biodegradability of the masterbatch obtained in Examples 1-3 are better than those in Comparative Examples 1-4. Specifically, it can be seen from the test results of Example 1 and Comparative Example 1 that the compatibilizer in this case is replaced with acrylic acid grafted polypropylene, and the antibacterial properties and biodegradability of the composite material are significantly reduced. It can be seen from the test results of Example 1 and Comparative Example 2 and Comparative Example 3 that the Ag and Cu bimetallic MOFs on the surface of MOFs-modified carbon fiber have a synergistic antibacterial effect. When MOFs-modified carbon fiber is prepared using a silver source or a copper source alone, the antibacterial property of the composite material is not ideal. It can be seen from the test results in Example 1 and Comparative Example 4 that the mechanical properties and antibacterial properties of the composite material are significantly reduced when the MOFs-modified carbon fiber is replaced with an acidified carbon fiber.

[0088] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A degradable and environmentally friendly modified plastic masterbatch, characterized in that: It includes the following raw materials in parts by weight: 100 parts of polypropylene, 40-50 parts of polylactic acid, 10-20 parts of MOFs modified carbon fiber, 5-10 parts of compatibilizer, 1-3 parts of antioxidant; The compatibilizer is 2-methacryloyloxyethyl phosphorylcholine grafted polypropylene.

2. The degradable and environmentally friendly modified plastic masterbatch according to claim 1, characterized in that: The preparation method of the compatibilizer comprises the following steps: Add polypropylene to a xylene solution of benzophenone, soak at 75°C for 45-60 minutes, take out, and vacuum dry for 1 hour in the dark to obtain pretreated polypropylene; Dissolve 2-methacryloyloxyethyl phosphorylcholine in degassed pure water to prepare a graft solution and transfer it to a glass container. Pass nitrogen to deoxygenate. Add pretreated polypropylene to the graft solution. Irradiate under ultraviolet light for 30-45 minutes and then filter. Wash the filter cake and dry it in vacuum.

3. The degradable and environmentally friendly modified plastic masterbatch according to claim 2, characterized in that: The dosage ratio of polypropylene and the xylene solution of benzophenone is 1g:30-50mL, the concentration of benzophenone in the xylene solution of benzophenone is 0.2mol / L, the dosage ratio of the graft solution and the pretreated polypropylene is 30-50mL:1g, and the concentration of 2-methacryloyloxyethyl phosphorylcholine in the graft solution is 0.5mol / L.

4. The degradable and environmentally friendly modified plastic masterbatch according to claim 1, characterized in that: The preparation method of the MOFs modified carbon fiber comprises the following steps: S1, adding silver nitrate, copper nitrate trihydrate, 5-hydroxyisophthalic acid, 2-methylimidazole, 1,10-phenanthroline and DMF into deionized water, and ultrasonically treating at room temperature for 30 minutes to obtain an electrophoresis solution; S2. Using the acidified carbon fiber as cathode and the metal copper rod as anode, electrophoretic deposition is performed on the surface of the acidified carbon fiber in an electrophoretic solution at room temperature. After the battery deposition, the acidified carbon fiber is dried at 60-90°C for 24 hours and chopped to a length of 3-7 mm to obtain MOFs modified carbon fiber.

5. The degradable and environmentally friendly modified plastic masterbatch according to claim 4, characterized in that: The dosage ratio of silver nitrate, copper nitrate trihydrate, 5-hydroxyisophthalic acid, 2-methylimidazole, 1,10-phenanthroline, DMF and deionized water in the electrophoresis solution is 25mmol:50mmol:50mmol:50mmol:1mmol:1L:0.33L.

6. The degradable and environmentally friendly modified plastic masterbatch according to claim 4, characterized in that: During the electrophoretic deposition process, the distance between the cathode and the anode is 1-5 cm, the voltage during electrodeposition is 4-10 V, and the deposition time is 30 min.

7. A method for preparing a degradable and environmentally friendly modified plastic masterbatch according to any one of claims 1 to 6, characterized in that: The following steps are involved: According to the formula ratio, polypropylene, polylactic acid, MOFs modified carbon fiber, compatibilizer and antioxidant are added to the mixer, stirred and mixed at a temperature of 25-40°C and a rotation speed of 150-300 rpm for 15-30 minutes, and then transferred to a twin-screw extruder for melt blending and extrusion granulation to obtain a degradable and environmentally friendly modified plastic masterbatch.

8. The method for preparing a degradable and environmentally friendly modified plastic masterbatch according to claim 7, characterized in that: The operating temperature of the twin-screw extruder is 170-190°C and the screw speed is 250-350rpm.

Citation Information

Patent Citations

  • Biodegradable antibacterial plastic master batch, preparation method thereof and antibacterial plastic product containing biodegradable antibacterial plastic master batch

    CN115418051A

Cited By

  • Bio-based degradable PP material and preparation method thereof

    CN120464072A

  • A biobased degradable pp material and a preparation method thereof

    CN120464072B

  • Full-biodegradable material based on carbon fibers and preparation method of full-biodegradable material

    CN120737564A